2020
DOI: 10.1038/s41598-020-58138-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization and in-silico analysis of Momordica charantia 7S globulin for stability and ACE inhibition

Abstract: Momordica charantia (Mc) seeds are widely used edible crop with high nutritional quality. The food and pharmaceutical industries use it as a natural anti-oxygenic agent. Herein, a ~52 kDa protein, which is a major part of seed proteome has been purified, biochemically characterized and structure has been determined. MALDI-ESI-MS identified peptide fragments and contig-deduced sequence suggested the protein to be homologous to 7S globulins. The crystal structure shows that protein has a bicupin fold similar to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…Molecular dynamics simulation of NTD with GMP, ZINC000257324845, ZINC000005169973 and ZINC000009913056 were performed to assess the structural and dynamics variation at an atomistic level. Protein topologies and coordinates files were generated using GROMACS 2019.2 along with GROMOS96 43a1 force field, as done by Kesari et al (2020), Singh et al (2018), van Gunsteren et al (1996), van der Spoel et al (2005. Total four systems (NTD-GMP, NTD-ZINC000257324845, NTD-ZINC000005169973 and NTD-ZINC000009913056) were generated and kept for molecular simulation of 100 ns.…”
Section: Molecular Dynamics and Mmpbsamentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular dynamics simulation of NTD with GMP, ZINC000257324845, ZINC000005169973 and ZINC000009913056 were performed to assess the structural and dynamics variation at an atomistic level. Protein topologies and coordinates files were generated using GROMACS 2019.2 along with GROMOS96 43a1 force field, as done by Kesari et al (2020), Singh et al (2018), van Gunsteren et al (1996), van der Spoel et al (2005. Total four systems (NTD-GMP, NTD-ZINC000257324845, NTD-ZINC000005169973 and NTD-ZINC000009913056) were generated and kept for molecular simulation of 100 ns.…”
Section: Molecular Dynamics and Mmpbsamentioning
confidence: 99%
“…Three chlorides (Cl -) ions were added using genion tool to neutralize the system. The final production run was done for 100 ns, and coordinates were updated every 10 ps, as done by Kesari et al (2020). The trajectories were analyzed by visual molecular dynamics (VMD) and XMGRACE (Humphrey et al, 1996).…”
Section: Molecular Dynamics and Mmpbsamentioning
confidence: 99%
“…In addition, lunasin was an effective adjuvant for immunization with OVA, which together improved animal survival against lethal challenge with influenza virus expressing the major histocompatibility complex (MHC) class I OVA peptide SIINFEKL (PR8-OTI) Preclinical in vivo [ 62 ] Equol 20 mg/kg for 3 days by gavage ( G. max ) In BALB/c mice treated with equol showed a significantly higher level of OVA-specific IgE. IL-13 (produced mainly by CD4⁺ T cells) production level was significantly higher than that control Preclinical in vivo [ 29 ] 7S globulin ( Momordica charantia L. – Cucurbitaceae) Study revealed that a tripeptide (VFK) from 7S globulin possess a higher binding affinity for ACE than reported drug Lisinopril (LPR) Not mentioned [ 42 ] Lectin 100 µg/ml ( M. charantia ) Lectin is a T cell-independent B cell activator and a polyclonal immunoglobulin (Ig) inducer in BALB/c mice. Additionally, lectin was shown to upregulate the cell activation marker CD86, in a B cell subpopulation Preclinical in vivo [ 63 ] MAP30 (anti-HIV protein) 1 µM ( M. charantia ) MAP30 was capable of inhibiting infection of HIV type 1 (HIV-1) in T lymphocytes and monocytes as well as replication of the virus in already-infected cells.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, extracts from Momordica spp. are useful for the treatment of various diseases and many other ailments due to the several biological activities exerted such as anti-diabetic Tan et al (2008) , Madala et al (2014) , Jia et al (2017) , Islam and Jalaluddin (2019) , Perera et al (2021) , Venugopal and Dhanasekaran (2021) , anti-oxidant Acquaviva et al (2013) , Ozusaglam and Karakoca (2013) , Huang et al (2020) , Perumal et al (2021) , anti-microbial ( Kumar et al (2009) , Patel et al (2010) , Gupta et al (2011) , anti-bacterial ( Koneri et al (2006) , Orhan et al (2010) , Leelaprakash et al (2011) , Puškárová et al (2017) , Chen et al (2019) , Islam and Jalaluddin (2019) , Khadijeh et al (2019) , anti-viral Orhan et al (2010) , Santhosh Kumar et al (2020) , anti-fungal Santos et al (2012) , anthelmintic Beloin et al (2005) , Jia et al (2017) , insecticidal Pari et al (2020) , antiglycation Chen et al (2011) , anti-inflammatory Chen et al (2019) , Khadijeh et al (2019) , Perera et al (2021) , Venugopal and Dhanasekaran (2021) , anti-thrombotic Patil and Rathod (2020) , anti-allergic Asna et al (2020) , hepatoprotective Ramalhete et al (2011) , estrogenic Badhwar et al (2020) , hypolipidemic effect Aeri and Raj (2020) , anti-carcinogenic Kesari et al (2020) , anti-proliferative Yue et al (2020) , anti-mutagenic Rolnik and Olas (2020) , and chemo-preventive activities ( Gupta, 2020 ).…”
Section: Introductionmentioning
confidence: 99%